Sedimentary architecture and optical dating of Middle and Late Pleistocene Rhine-Meuse deposits - Fluvial response to climate change, sea-level fluctuation and glaciation: - Busschers, F.S.; Weerts, H.J.T.; Wallinga, J.; Cleveringa, P.; Kasse, C.; Wolf, H.de; Cohen, K.M. (2005)
Eight continuous corings in the west-central Netherlands show a 15 to 25 m thick stacked sequence of sandy to gravelly channel-belt deposits of the Rhine-Meuse system. This succession of fluvial sediments was deposited under net subsiding conditions in the southern part of the North Sea Basin and documents the response of the Rhine-Meuse river system to climate and sea-level change and to the glaciation history. On the basis of grain size characteristics, sedimentological structures, nature and extent of bounding surfaces and palaeo-ecological data, the sequence was subdivided into five fluvial units, an estuarine and an aeolian unit. Optical dating of 34 quartz samples showed that the units have intra Saalian to Weichselian ages (Marine Isotope Stages 8 to 2). Coarse-grained fluvial sediments primarily deposited under cold climatic conditions, with low vegetation cover and continuous permafrost. Finer-grained sediments generally deposited during more temperate climatic conditions with continuous vegetation cover and/or periods of sea-level highstand. Most of the sedimentary units are bounded by unconformities that represent erosion during periods of climate instability, sea-level fall and/or glacio-isostatic uplift.